Bridging Business Models and Supply Chain Strategy: A Qualitative Synthesis of Value Creation Through Orchestration - Grace Yulianti; Seger Santoso (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review explores the intersection of business models and supply chain strategy through the lens of orchestration. Drawing from recent theoretical and empirical studies, the review identifies how orchestration enables firms to create value by dynamically aligning resources, coordinating stakeholders, and leveraging digital platforms in complex, uncertain environments. The findings emphasize three core mechanisms of orchestration—platform coordination, strategic integration, and resource reconfiguration—as essential for achieving agility and ecosystem-wide innovation. By synthesizing insights from both strategic management and supply chain literature, this study contributes to a more integrated understanding of how business model design shapes and is shaped by orchestration practices across industries